Evaluating media framing and public reactions in the context of a water reuse proposal. Issue 6 (2nd November 2018) - Goodwin, Daniel; Raffin, Marie; Jeffrey, Paul; Smith, Heather M.
ABSTRACT: The public is increasingly engaging with information about water reuse proposals through the Internet. Though there are benefits to engaging the public online, there may also be challenges associated with media bias or online advocacy. This study qualitatively examines the public response (online comments, n = 1323) to online news reporting an indirect potable reuse proposal for London. The study found no evidence of the media's framing of the event strongly shaping the unsolicited online public reactions. Findings suggest that though communications may struggle to counter longer-term news agendas, there may be benefits to experimenting with framing water safety measures and shorter-term gains.